EVALUATION OF EXISTING GAPS AND BRIDGING SKILLS GAP IN NON-TEACHING STAFF OF UNDERGRADUATE COURSE UNIVERSITIES (Journal of Pharmaceutical Negative Results, 2023)
Employers and the industry as a whole are extremely concerned about the employability of engineering graduates. Because of this, the quality of the product that comes from engineering colleges is important, and it must be the kind of product that possesses particular qualities and qualities that can be relied upon. The technical education system requires a complete overhaul in addition to modifications that must be implemented in the individual parts of the system. The purpose of this article is to investigate the skill gaps that exist between the non-teaching staff of academic programmes offered by universities and the industrial applications of information technology (curriculum). It investigates some of the factors that contributed to the gap, as well as some of the potential ways in which it could be closed. Skill gap analysis provides insights into your entire workforce, it helps with strategic workforce planning, it improves recruitment efforts, it generates a competitive edge, and it helps individuals learn and develop more effectively.